Characteristics of smallholder farm households in Upper Egypt: Implications for nutrition-sensitive agricultural interventions - El-Enbaby, Hoda; Ecker, Olivier; Figueroa, Jose Luis; Leroy, Jef L.; Breisinger, Clemens (International Food Policy Research Institute, 2019)
This paper characterizes smallholder farm households in Upper Egypt based on data from a comprehensive farm household survey. The results from the descriptive analysis in combination with findings from the global literature provide recommendations on how agricultural projects can be leveraged for improving nutrition. The importance of focusing on nutrition is underlined by relatively high undernutrition and overnutrition rates among the surveyed farm households: almost 18 percent of children under five years of age are stunted and almost 25 percent of them are at risk of being overweight. Agricultural interventions can impact nutrition through six main pathways, which are: 1) providing direct access to food from own production; 2) providing a source of income from which food and other nutrition needs can be met; 3) affecting food prices; 4) affecting women’s social status and empowerment; 5) affecting women’s time use from participation in agricultural work; and 6) affecting women’s health and nutrition from engagement in agricultural activities. The surveyed farm households purchase in the market most of the foods that they consume, cultivating crops primarily for commercial sale. This finding suggests that access to food markets and the level of food prices are key determinants of food and nutrition security among smallholder farm households in Upper Egypt. The survey analysis also identified potential levers for increasing agricultural productivity, including promoting more efficient use of water, fertilizers, and pesticides and improving farming practices to narrow the productivity gap between small-scale farmers and medium and large-scale farmers. As the role of women in agricultural activities in Upper Egypt is limited, the gendered pathways for leveraging agriculture for improved nutrition are less relevant. However, to achieve positive impact on people’s diet or nutritional status that goes beyond income and price channels, programs that reach farm households in Upper Egypt should include education and behavioral change communication activities, including on themes related to breastfeeding, dietary diversity, physical activities, and sugar intake. For such activities to be effective, it is important to consider the low literacy levels in the population.